Electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery using said electrode
Patent Information
- Application Number
- JP2021548814
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-14
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2040-09-14
AI Technical Summary
【0009】 本発明によれば、結着剤の含量の少ない電極活物質合剤層(以下「電極合剤層」とも称する)を有する非水電解質二次電池用電極を提供することができ、電極の単位質量当たりの充放電容量を大きくできる。
Smart Images

Figure 0007641227000001 
Figure 0007641227000002 
Figure 0007641227000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a non-aqueous electrolyte secondary battery in which an electrode active material mix layer containing an electrode active material and a binder is formed on a current collector, and to a non-aqueous electrolyte secondary battery using the electrode. [Background technology]
[0002] Lithium-ion secondary batteries are small, lightweight, have a high energy density, a high capacity, and can be repeatedly charged and discharged, and therefore are widely used as power sources for portable electronic devices such as portable personal computers, handheld video cameras, information terminals, etc. In addition, from the perspective of environmental issues, electric vehicles using lithium-ion secondary batteries and hybrid vehicles that use electricity as part of their motive power are being put to practical use.
[0003] lithium ion In the electrodes of secondary batteries, a coating method is generally used in which an electrode active material, a binder, and a conductive assistant are dispersed in a solvent to form a slurry, and the slurry is applied to a current collector and dried to form an electrode active material mixture layer on the current collector. The less the binder and conductive assistant among the components constituting the electrode active material mixture layer, the greater the battery capacity per unit mass, and a high-capacity battery can be obtained. On the other hand, since the binder is a component that bonds particles to particles and particles to a current collector, if the binding is insufficient due to a lack of binder, etc., the electrode mixture layer is likely to crack or peel off, which not only reduces the capacity of the battery but also may cause an internal short circuit in the battery. For this reason, it was difficult to prepare an electrode with an extremely low binder content by the coating method.
[0004] In response to this, methods have been proposed for producing an electrode having an electrode mixture layer that does not contain a binder by colliding fine particles of an electrode active material with a current collector at high speed using a cold spray method or an aerosol deposition method (see, for example, Patent Documents 1 and 2). However, these methods have problems such as the need for a large device, high energy consumption, low productivity due to a slow film formation speed, and a tendency for composition fluctuations to occur. In addition, while the cold spray method and the aerosol deposition method can be applied to electrode active materials with a relatively high hardness, it is difficult to produce a thick electrode mixture layer in the case of an organic sulfur-based electrode active material, which is an electrode active material with a low hardness.
[0005] On the other hand, organic sulfur-based electrode active materials obtained by heat-treating a mixture of an organic compound and sulfur under a non-oxidizing atmosphere are known as electrode active materials that have a large charge / discharge capacity and are less likely to decrease in charge / discharge capacity due to repeated charging and discharging (see, for example, Patent Documents 3 to 15). Organic sulfur-based electrode active materials have been mainly studied as positive electrode active materials, but can also be used as negative electrode active materials (see, for example, Patent Documents 11 to 12). However, among electrodes manufactured by a coating method using an organic sulfur-based electrode active material as the electrode active material, no electrodes have been known in which the binder content in the electrode active material mixture layer is 0.4 mass% or less. In addition, the hardness of organic sulfur-based electrode active materials is insufficient to apply the cold spray method or the aerosol deposition method. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-310502 A [Patent Document 2] JP2008-184647A [Patent Document 3] JP 2003-151550 A [Patent Document 4] International Publication No. 2010 / 044437 [Patent Document 5] JP 2011-028948 A [Patent Document 6] JP 2011-170991 A [Patent Document 7] JP 2012-099342 A [Patent Document 8] JP 2012-150933 A [Patent Document 9] JP 2012-150934 A [Patent Document 10] International Publication No. 2012 / 114651 [Patent Document 11] JP 2014-096326 A [Patent Document 12] JP 2014-096327 A [Patent Document 13] JP 2015-092449 A [Patent Document 14] International Publication No. 2016 / 158675 [Patent Document 15] International Publication No. 2016 / 159212 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an electrode for a non-aqueous electrolyte secondary battery having an electrode active material mix layer with a small binder content in order to increase the charge / discharge capacity per unit mass of the electrode. [Means for solving the problem]
[0008] As a result of intensive research into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using an organic sulfur-based electrode active material as an electrode active material, and have completed the present invention. That is, the present invention includes a current collector, and an electrode active material mixture layer containing an organic sulfur-based electrode active material, a conductive assistant, and a binder, and the binder is present in an amount of 0.01% by mass to 100% by mass relative to the total mass of the electrode active material mixture layer. 0.4 % by mass, and the electrode active material mixture layer is formed on the current collector. Effect of the Invention
[0009] According to the present invention, it is possible to provide an electrode for a nonaqueous electrolyte secondary battery having an electrode active material mixture layer (hereinafter also referred to as "electrode mixture layer") with a small binder content, thereby making it possible to increase the charge / discharge capacity per unit mass of the electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In the present invention, an organic sulfur-based electrode active material is used as the electrode active material. In the present invention, the organic sulfur-based electrode active material refers to a compound that has a sulfur-carbon bond, can absorb and release lithium ions, and can be used as an electrode active material for a secondary battery. The organic sulfur-based electrode active material is a compound obtained by heat treating a mixture of an organic compound and sulfur under a non-oxidizing atmosphere, and examples of the organic sulfur-based electrode active material include sulfur-modified polyacrylonitrile, sulfur-modified elastomer compound, sulfur-modified polynuclear aromatic ring compound, sulfur-modified pitch compound, polythienoacene compound, sulfur-modified polyether compound, sulfur-modified polyamide compound, sulfur-modified aliphatic hydrocarbon oxide, and polycarbon sulfide.
[0011] The sulfur-modified polyacrylonitrile is a compound obtained by heat-treating polyacrylonitrile and elemental sulfur in a non-oxidizing atmosphere. The polyacrylonitrile may be a homopolymer of acrylonitrile. It may also be a copolymer of acrylonitrile and another monomer. When the polyacrylonitrile is a copolymer, the content of acrylonitrile in the copolymer is preferably at least 90% by mass or more, since the battery performance decreases when the content of acrylonitrile is low. Examples of other monomers include acrylic acid, vinyl acetate, N-vinylformamide, and N,N'-methylenebisacrylamide.
[0012] The blending ratio of polyacrylonitrile and elemental sulfur in the heat treatment is preferably 100 parts by mass to 1500 parts by mass of elemental sulfur per 100 parts by mass of polyacrylonitrile, more preferably 150 parts by mass to 1000 parts by mass. The temperature of the heat treatment is preferably 250°C to 550°C, more preferably 350°C to 450°C. Since unreacted elemental sulfur is a factor that reduces the cycle characteristics of a secondary battery, it is preferable to remove it from the sulfur-modified polyacrylonitrile, for example, by heating or solvent washing after the heat treatment. The sulfur content of the sulfur-modified polyacrylonitrile is preferably 25% by mass to 70% by mass, more preferably 30% by mass to 55% by mass, since a large charge / discharge capacity can be obtained. The sulfur content of the organic sulfur-based electrode active material can be calculated from the analysis results using a CHN analyzer capable of analyzing sulfur and oxygen. The weight average molecular weight of the polyacrylonitrile used in the present invention is not particularly limited, and commercially available polyacrylonitrile can be used.
[0013] The sulfur-modified elastomer compound is a compound obtained by heat-treating rubber and elemental sulfur in a non-oxidizing atmosphere. Examples of rubber include natural rubber, isoprene rubber, butadiene rubber, styrene butadiene rubber, and acrylonitrile butadiene rubber. These rubbers may be used alone or in combination of two or more. The raw rubber may be vulcanized rubber or rubber before vulcanization.
[0014] The blending ratio of rubber and elemental sulfur in the heat treatment is preferably 100 to 1500 parts by mass of elemental sulfur per 100 parts by mass of rubber, more preferably 150 to 1000 parts by mass. When the heat treatment is performed, one or more known vulcanization accelerators can be added. The amount of the vulcanization accelerator added is preferably 1 to 250 parts by mass, more preferably 5 to 50 parts by mass, per 100 parts by mass of rubber. The heat treatment temperature is preferably 250°C to 550°C, more preferably 300°C to 450°C. Since unreacted elemental sulfur is a factor that reduces the cycle characteristics of the secondary battery, it is preferable to remove it from the sulfur-modified elastomer compound, for example, by heating or solvent washing. The sulfur content of the sulfur-modified elastomer compound is preferably 40% to 70% by mass, more preferably 45% to 60% by mass, since a large charge / discharge capacity can be obtained.
[0015] The sulfur-modified polynuclear aromatic ring compound is a compound obtained by heat-treating a polynuclear aromatic ring compound and elemental sulfur in a non-oxidizing atmosphere. Examples of polynuclear aromatic ring compounds include naphthalene, anthracene, tetracene, pentacene, phenanthrene, chrysene, picene, pyrene, benzopyrene, perylene, coronene, and other benzene-based aromatic ring compounds. Examples of other polynuclear aromatic ring compounds include aromatic ring compounds in which a portion of a benzene-based aromatic ring compound is a 5-membered ring, and heteroatom-containing heteroaromatic ring compounds in which a portion of the carbon atoms of these compounds are replaced by sulfur, oxygen, nitrogen, or the like. Furthermore, these polynuclear aromatic ring compounds may have a substituent such as a linear or branched alkyl group having 1 to 12 carbon atoms, an alkoxyl group, a hydroxyl group, a carboxyl group, an amino group, an aminocarbonyl group, an aminothio group, a mercaptothiocarbonylamino group, or a carboxyalkylcarbonyl group.
[0016] The polynuclear aromatic ring compound may be a compound having a repeating structure of an aromatic moiety and a chain hydrocarbon moiety. Examples of the aromatic moiety of the compound having a repeating structure of an aromatic moiety and a chain hydrocarbon moiety include, in addition to the above, benzene, pyrrolidine, pyrrole, pyridine, imidazole, pyrrolidone, tetrahydrofuran, triazine, thiophene, oxazole, thiazole, thiadiazole, triazole, phosphole, silole, etc. part These aromatic moieties may be condensed with cyclopentane, cyclohexane, pyrrolidine, tetrahydrofuran, etc. These aromatic moieties may have a substituent such as a linear or branched alkyl group having 1 to 12 carbon atoms, an alkoxyl group, a hydroxyl group, a carboxyl group, an amino group, an aminocarbonyl group, an aminothio group, a mercaptothiocarbonylamino group, or a carboxyalkylcarbonyl group.
[0017] Examples of the chain hydrocarbon moiety of the compound having a repeating structure of an aromatic moiety and a chain hydrocarbon moiety include linear or branched chain hydrocarbons such as alkylene groups, alkenylene groups, and alkynylene groups. The number of carbon atoms in the chain hydrocarbon moiety is preferably 2 to 20, more preferably 3 to 10, and even more preferably 4 to 8. From the viewpoint of ease of handling and economical efficiency, alkylene groups or alkenylene groups are preferred, and among them, butane-1,4-diyl group, hexane-1,6-diyl group, octane-1,8-diyl group, vinylene group, 1,3-butadiene-1,4-diyl group, and structural isomers thereof are preferred.
[0018] The blending ratio of the polynuclear aromatic ring compound and the elemental sulfur in the heat treatment is preferably 100 to 1500 parts by mass of elemental sulfur per 100 parts by mass of the polynuclear aromatic ring compound, more preferably 150 to 1000 parts by mass. The temperature of the heat treatment is preferably 250°C to 550°C, more preferably 300°C to 450°C. Since unreacted elemental sulfur is a factor that reduces the cycle characteristics of the secondary battery, it is preferable to remove it from the sulfur-modified polynuclear aromatic ring compound by, for example, heating or solvent washing. The sulfur content of the sulfur-modified polynuclear aromatic ring compound is preferably 40% to 70% by mass, more preferably 45% to 60% by mass, since a large charge / discharge capacity can be obtained.
[0019] The sulfur-modified pitch compound is a compound obtained by heat-treating pitches and elemental sulfur in a non-oxidizing atmosphere. Examples of pitches include petroleum pitch, coal pitch, mesophase pitch, asphalt, coal tar, coal tar pitch, organic synthetic pitch obtained by polycondensation of condensed polycyclic aromatic hydrocarbon compounds, and organic synthetic pitch obtained by polycondensation of heteroatom-containing condensed polycyclic aromatic hydrocarbon compounds. Pitches are mixtures of various compounds, and condensed polycyclic aromatic hydrocarbon compounds are generally used. compound Condensed polycyclic aromatic compounds contained in pitches compound The condensed polycyclic aromatic compound may be of a single type or of multiple types. compound may contain nitrogen or sulfur in the ring in addition to carbon and hydrogen. Therefore, the main component of coal pitch is considered to be a mixture of condensed polycyclic aromatic hydrocarbons consisting only of carbon and hydrogen, and heteroaromatic compounds containing nitrogen, sulfur, etc. in the condensed ring.
[0020] The blending ratio of pitches and elemental sulfur in the heat treatment is preferably 100 parts by mass to 1000 parts by mass of elemental sulfur per 100 parts by mass of pitches, more preferably 150 parts by mass to 500 parts by mass. The temperature of the heat treatment is preferably 300°C to 500°C, more preferably 350°C to 500°C. Unreacted elemental sulfur is a factor that reduces the cycle characteristics of a secondary battery, so it is preferable to remove it from the sulfur-modified pitch compound by, for example, heating or solvent washing. The sulfur content of the sulfur-modified pitch compound is preferably 25% by mass to 70% by mass, more preferably 30% by mass to 60% by mass, because a large charge / discharge capacity can be obtained.
[0021] The polythienoacene compound is a compound having a sulfur-containing polythienoacene structure represented by the following general formula (1).
[0022] [ka] (In the formula, * represents a bond.)
[0023] The polythienoacene compound can be obtained by heat treating an aliphatic polymer compound having a linear chain structure, such as polyethylene, or a polymer compound having a thiophene structure, such as polythiophene, with elemental sulfur in a non-oxidizing atmosphere.
[0024] When an aliphatic polymer compound having a linear structure is used as the raw material of the polythienoacene compound, the blending ratio of the aliphatic polymer compound and the elemental sulfur is preferably 100 to 2000 parts by mass of elemental sulfur per 100 parts by mass of the aliphatic polymer compound, more preferably 150 to 1000 parts by mass. When a polymer compound having a thiophene structure is used as the raw material, the blending ratio of the polymer compound having a thiophene structure and the elemental sulfur is preferably 100 to 1000 parts by mass of elemental sulfur per 100 parts by mass of the polymer compound having a thiophene structure, more preferably 150 to 800 parts by mass. The temperature of the heat treatment is preferably 300°C to 600°C, more preferably 350°C to 500°C. Unreacted elemental sulfur is a factor that reduces the cycle characteristics of the secondary battery, so it is preferable to remove it from the polythienoacene compound by, for example, heating or solvent washing. The sulfur content of the polythienoacene compound is preferably from 30% by mass to 80% by mass, and more preferably from 40% by mass to 70% by mass, since a large charge / discharge capacity can be obtained.
[0025] The sulfur-modified polyether compound is a compound obtained by heat-treating a polyether compound and elemental sulfur in a non-oxidizing atmosphere. Examples of the polyether compound include polyethylene glycol, polypropylene glycol, ethylene oxide / propylene oxide copolymer, polytetramethylene glycol, etc. The polyether compound may have an alkyl ether group, an alkylphenyl ether group, or an acyl group at the end, or may be an ethylene oxide adduct of a polyol such as glycerin or sorbitol.
[0026] The blending ratio of the polyether compound and the elemental sulfur in the heat treatment is preferably 100 to 1000 parts by mass of elemental sulfur per 100 parts by mass of the polyether compound, more preferably 200 to 500 parts by mass. The temperature of the heat treatment is preferably 250°C to 500°C, more preferably 300°C to 450°C. Unreacted elemental sulfur is a factor that reduces the cycle characteristics of the secondary battery, so it is preferable to remove it from the sulfur-modified polyether compound, for example, by heating or washing with a solvent. The sulfur content of the sulfur-modified polyether compound is preferably 30% to 75% by mass, more preferably 40% to 70% by mass, because a large charge / discharge capacity can be obtained.
[0027] The sulfur-modified polyamide compound is an organic sulfur compound having a carbon skeleton derived from a polymer having an amide bond, and specifically, is a compound obtained by heat-treating an aminocarboxylic acid compound and elemental sulfur, or a polyamine compound, a polycarboxylic acid compound and elemental sulfur, in a non-oxidizing atmosphere.
[0028] In the present invention, the aminocarboxylic acid compound refers to a compound having one amino group and at least one carboxyl group in the molecule. Examples of the aminocarboxylic acid compound include aminobenzoic acids such as 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, p-aminobenzoic acid, and m-aminobenzoic acid, 4-aminophenylacetic acid, 3-aminophenylacetic acid, 3-(4-aminophenyl)propionic acid, 3-aminopropionic acid, 4-aminobutanoic acid, 5-aminopentanoic acid, and 2,5-diaminopentanoic acid, as well as amino acids such as alanine, arginine, asparagine, aspartic acid, cysteine, glutamine, glutamic acid, glycine, histidine, isoleucine, leucine, lysine, methionine, phenylalanine, proline, serine, threonine, tryptophan, tyrosine, valine, theanine, tricolominic acid, kainic acid, domoic acid, ibotenic acid, and acromelic acid.
[0029] In the present invention, the polyamine compound refers to a compound having at least two amino groups in the molecule, such as urea, ethylenediamine, diethylenetriamine, putrescine, cadaverine, hexamethylenediamine, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 4-aminobenzenemethanamine, 4-aminobenzeneethanamine, melamine, 1,2,4-triaminobenzene, 1,3,5-triaminobenzene, and benzoguanamine.
[0030] In the present invention, the polycarboxylic acid compound refers to a compound having at least two carboxyl groups in the molecule. Examples of the polycarboxylic acid compound include terephthalic acid, fumaric acid, tartaric acid, maleic acid, benzene-1,3-dicarboxylic acid, phthalic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and ethylenediaminetetraacetic acid. In addition, phthalic anhydride, maleic anhydride, and the like may be mentioned, and may be an acid anhydride. When a sulfur-modified polyamide compound is produced using a polyamine compound and a polycarboxylic acid compound, the ratio of the polyamine compound to the polycarboxylic acid compound is preferably 0.9 to 1.1 in molar ratio.
[0031] In the heat treatment, the ratio of the amino carboxylic acid compound and the elemental sulfur is preferably 100 to 500 parts by mass of the elemental sulfur per 100 parts by mass of the amino carboxylic acid compound, more preferably 150 to 400 parts by mass. The blending ratio of the polyamine compound, the polycarboxylic acid compound, and the elemental sulfur is preferably 100 to 500 parts by mass of the elemental sulfur per 100 parts by mass of the total mass of the polyamine compound and the polycarboxylic acid compound, more preferably 150 to 400 parts by mass. The temperature of the heat treatment is preferably 250°C to 600°C, more preferably 350°C to 500°C. Since unreacted elemental sulfur is a factor that reduces the cycle characteristics of the secondary battery, it is preferable to remove it from the sulfur-modified polyamide compound by, for example, heating or solvent washing. The sulfur content of the sulfur-modified polyamide compound is preferably 40% by mass to 70% by mass, more preferably 45% by mass to 60% by mass, because a large charge / discharge capacity can be obtained.
[0032] The sulfur-modified aliphatic hydrocarbon oxide is a compound obtained by heat-treating an aliphatic hydrocarbon oxide and elemental sulfur in a non-oxidizing atmosphere. In the present invention, the aliphatic hydrocarbon oxide refers to a compound having an aliphatic hydrocarbon skeleton and at least one group selected from the group consisting of a hydroxyl group, a carbonyl group, a carboxyl group, or an epoxy group, and the hydrocarbon skeleton may have an unsaturated bond. The aliphatic hydrocarbon skeleton of the aliphatic hydrocarbon oxide may be linear or branched, but is preferably linear because a large charge / discharge capacity can be obtained. The carbon number of the aliphatic hydrocarbon oxide is preferably 4 to 12, more preferably 6 to 10, because a large charge / discharge capacity can be obtained. Since the oxygen atoms in the aliphatic hydrocarbon oxide are released by heat treatment with elemental sulfur, the aliphatic hydrocarbon oxide preferably has a ratio of the number of carbon atoms to the number of oxygen atoms of 3 or more, more preferably 4 or more.
[0033] Preferred aliphatic hydrocarbon oxides include alcohol compounds such as 1-butanol, 2-butanol, 1-pentanol, 3-pentanol, 1-hexanol, 1-heptanol, 1-octanol, 1-nonanol, 1-decanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, 2-octanol, 1-nonanol, and 1-decanol; aldehyde compounds such as butanal, pentanal, hexanal, heptanal, octanal, nonanal, and decanal; ketone compounds such as methyl ethyl ketone, diethyl ketone, and methylhexyl ketone; carboxylic acid compounds such as octanoic acid, nonanoic acid, and decanoic acid; and epoxy compounds such as 1,2-butane oxide, 1,2-hexane oxide, 1,2-octane oxide, and 1,2-decane oxide.
[0034] The mixing ratio of the aliphatic hydrocarbon oxide and elemental sulfur in the heat treatment is preferably 100 to 1000 parts by mass of elemental sulfur per 100 parts by mass of the aliphatic hydrocarbon oxide, more preferably 200 to 500 parts by mass. The temperature of the heat treatment is preferably 300 to 500°C, more preferably 350 to 450°C. When the temperature of the heat treatment is higher than the boiling point of the aliphatic hydrocarbon oxide, it is preferable to produce the aliphatic hydrocarbon oxide while refluxing it. Since unreacted elemental sulfur is a factor that deteriorates the cycle characteristics of the secondary battery, it is preferable to remove it from the sulfur-modified aliphatic hydrocarbon oxide by, for example, heating or solvent washing. The sulfur content of the sulfur-modified aliphatic hydrocarbon oxide is preferably 45 to 75% by mass, more preferably 50 to 70% by mass, since a large charge / discharge capacity can be obtained.
[0035] Polycarbon sulfide has the general formula (CS x ) n(x is 0.5 to 2, and n is a number of 4 or more), and can be obtained by, for example, heating a precursor obtained by reacting a complex of an alkali metal sulfide such as sodium sulfide and elemental sulfur with a halogenated unsaturated hydrocarbon such as hexachlorobutadiene. The heat treatment temperature is preferably 320°C to 400°C, and the sulfur content of the polycarbonate compound is preferably 65% by mass to 75% by mass because a large charge / discharge capacity can be obtained.
[0036] When the heat treatment of the organic compound and sulfur is carried out in a non-oxidizing atmosphere, the non-oxidizing atmosphere can be an atmosphere in which the oxygen concentration in the gas phase is 5% by volume or less, preferably 2% by volume or less, and more preferably an atmosphere substantially free of oxygen, such as an inert gas atmosphere such as nitrogen, helium, or argon, or a sulfur gas atmosphere.
[0037] The organic compound and sulfur, which are the raw materials for the organic sulfur-based electrode active material, are mixed and heat-treated after being finely divided as necessary. Since an organic sulfur-based electrode active material with little variation in quality can be obtained, it is preferable that the organic compound and sulfur are mixed even during the heat treatment. Examples of the mixing method include container rotation type mixing, in which the heating container itself is rotated to mix, and stirring and mixing by a stirring blade inserted into the heating container. Examples of heat treatment devices for container rotation type mixing include rotary kilns, and examples of heat treatment devices for stirring and mixing include heat treatment devices having screw blades, helical ribbon blades, and the like. The heat treatment device for stirring and mixing may be a vertical device having a bottom, or a horizontal device such as a tunnel structure. As a mixing method during heat treatment, a container rotation type mixing heat treatment device is preferable because an active material with excellent battery characteristics can be obtained. The reason why an active material with excellent battery characteristics can be obtained when a container rotation type mixing device is used is unclear, but it is presumed that in the stirring and mixing device, the intermediate of the organic sulfur-based electrode active material is subjected to a load such as compression by the stirring blade during heat treatment.
[0038] The particle diameter of the organic sulfur-based electrode active material is preferably 0.1 μm to 50 μm in terms of average particle diameter. The particle diameter is a diameter based on volume, and the diameter of secondary particles is measured by the laser diffraction light scattering method. In the present invention, the average particle diameter is the 50% particle diameter (D 50 ) In order to reduce the average particle size of the organic sulfur-based electrode active material to less than 0.1 μm, a great deal of effort is required, but further improvement in battery performance cannot be expected, and if it is greater than 50 μm, peeling of the electrode mixture layer may easily occur. The average particle size of the organic sulfur-based electrode active material is more preferably 0.5 μm to 30 μm, and further preferably 1 μm to 20 μm.
[0039] The specific surface area of the organic sulfur-based electrode active material is 0.5 m 2 / g~30m 2 In the present invention, the specific surface area refers to a specific surface area measured by the BET (Brunauer-Emmett-Teller) method. 2 If the capacity is less than 30m / g, sufficient charge / discharge capacity may not be obtained. 2 If the specific surface area is greater than 1 m / g, the binding property becomes insufficient and excellent cycle characteristics may not be obtained. 2 / g~20m 2 / g is more preferable, and 3m 2 / g~15m 2 / g is more preferred.
[0040] As the conductive assistant for the electrode having an electrode mixture layer containing an organic sulfur-based electrode active material, any of those known as conductive assistants for electrodes of nonaqueous electrolyte secondary batteries can be used. Specifically, natural graphite, artificial graphite, carbon black, ketjen black, acetylene black, channel black, furnace black, lamp black, thermal black, carbon nanotubes, vapor grown carbon fiber (VGCF), ThinExamples of the conductive assistant include carbon materials such as exfoliated graphite, expanded graphite, graphene, fullerene, and needle coke; metal powders such as aluminum powder, nickel powder, and titanium powder; conductive metal oxides such as zinc oxide and titanium oxide; and sulfides such as La2S3, Sm2S3, Ce2S3, and TiS2. The particle size of the conductive assistant is preferably 0.0001 μm to 50 μm, and more preferably 0.01 μm to 40 μm. If the content of the conductive assistant is too small, the conductivity of the electrode mixture layer may be insufficient and sufficient capacity may not be obtained, and if the content of the conductive assistant is too large, the content of the organic sulfur-based electrode active material may be reduced and the capacity may be reduced. Therefore, the content of the conductive assistant is preferably 1 part by mass to 30 parts by mass, and more preferably 2 parts by mass to 20 parts by mass, relative to 100 parts by mass of the organic sulfur-based electrode active material.
[0041] The electrode mixture layer of the electrode for a non-aqueous electrolyte secondary battery of the present invention contains a binder in an amount of 0.4 mass % or less. Examples of binders that can be used in the electrode of the present invention include polydiene binders such as ethylene-propylene-diene rubber, styrene-butadiene rubber, butadiene rubber, acrylonitrile butadiene rubber, and styrene-isoprene rubber. arrivalagents; polycarboxylic acid-based binders such as polyacrylic acid, polymethyl methacrylate, polyacrylate, ethylene-acrylic acid copolymer, and ethylene-methacrylic acid copolymer; polyolefin-based binders such as polyethylene, polypropylene, and propylene-α-olefin copolymer; fluorinated polymer-based binders such as polyvinylidene fluoride and polytetrafluoroethylene; polydiene-based binders such as butadiene rubber, styrene-butadiene rubber, acrylonitrile butadiene rubber, styrene-isoprene rubber, and ethylene-propylene-diene rubber; polyether-based binders such as polyethylene oxide and modified polyphenylene oxide; polyamide resins, polyimide resins, Examples of binders include amide-imide-based binders such as polyamide-imide resins; cellulose-based binders such as carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, cellulose nanofiber, and cellulose nanocrystals; polyvinyl alcohol-based binders such as polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and polyvinyl acetate; polyacrylonitrile-based binders such as polyacrylonitrile; polyester-based binders such as polyester polyol; and polyurethane-based binders. In the case of a binder having an acidic group such as a carboxyl group, the binder may be neutralized with an alkali metal such as lithium, sodium, or potassium.
[0042] The binder may be used alone or in combination of two or more. As the binder, polyolefin-based binders, polydiene-based binders, polycarboxylic acid-based binders, polyether-based binders, polyvinyl alcohol-based binders, polyacrylonitrile-based binders, cellulose-based binders, polyester-based binders, and polyurethane-based binders are preferred because they provide high binding properties even in small amounts.
[0043] When the content of the binder in the electrode mixture layer is small, sufficient binding properties cannot be obtained, so the electrode mixture layer of the present invention contains 0.01 mass% or more relative to its total mass. On the other hand, when the amount of the binder in the electrode mixture layer is large, the electric capacity of the electrode decreases, so the electrode mixture layer contains 0.4 mass% or less of the binder relative to the total mass. The content of the binder in the electrode mixture layer is preferably 0.05 mass% to 0.4 mass%, more preferably 0.1 mass% to 0.4 mass%.
[0044] The electrode of the present invention is prepared by adding an organic sulfur-based electrode active material and a conductive assistant to a solvent, and further adding a binder to prepare a slurry, which is then applied to a current collector and dried to form an electrode mixture layer. Examples of the solvent include dimethyl carbonate, acetonitrile, tetrahydrofuran, N-methylpyrrolidone, N,N-dimethylformamide, methyl ethyl ketone, cyclohexanone, ethyl acetate, butyl acetate, tetrahydrofuran, ethanol, water, etc., and among these, N-methylpyrrolidone, ethanol, and water are preferred. Examples of the method for preparing the slurry include a ball mill, a rotation / revolution mixer, a planetary mixer, and a disperser.
[0045] If the electrode mixture layer is too thin, sufficient charge / discharge capacity cannot be obtained, whereas if it is too thick, diffusion of alkali metal ions into the electrode mixture layer becomes insufficient or the electrode mixture layer becomes prone to cracking or peeling. Therefore, the thickness of the electrode mixture layer per side is preferably 10 μm to 500 μm, and more preferably 40 μm to 300 μm.
[0046] The current collector is made of a conductive material such as titanium, a titanium alloy, aluminum, an aluminum alloy, copper, nickel, stainless steel, nickel-plated steel, carbon, etc. The thickness of the current collector is usually about 5 μm to 50 μm, for example, about 7 μm to 30 μm in the case of aluminum or an aluminum alloy, and about 5 μm to 15 μm in the case of copper or a copper alloy.
[0047] After drying, the electrode having the electrode mixture layer containing the organic sulfur-based electrode active material may be subjected to a pressing treatment as necessary. Examples of the pressing method include a mold pressing method and a roll pressing method.
[0048] The electrode having an electrode mixture layer containing an organic sulfur-based electrode active material is electrolyte It may be used as a positive electrode or a negative electrode of a secondary battery. When an electrode having an electrode mixture layer containing an organic sulfur-based electrode active material is used as a positive electrode of a lithium-ion secondary battery, an electrode having a known negative electrode active material may be used as a negative electrode, and when used as a negative electrode, an electrode having a known positive electrode active material may be used as a positive electrode. In the present invention, the negative electrode when an electrode having an organic sulfur-based electrode active material as an electrode active material is used as a positive electrode is called a counter electrode, and the positive electrode when used as a negative electrode is called a counter electrode.
[0049] Known negative electrode active materials used when an electrode using an organic sulfur-based electrode active material as an electrode active material is used as a positive electrode and a counter electrode is a negative electrode include, in the case of a lithium ion secondary battery, for example, natural graphite, artificial graphite, non-graphitizable carbon, easily graphitizable carbon, lithium, lithium alloys, silicon, silicon alloys, silicon oxide, tin, tin alloys, tin oxide, phosphorus, germanium, indium, copper oxide, antimony sulfide, titanium oxide, iron oxide, manganese oxide, cobalt oxide, nickel oxide, lead oxide, ruthenium oxide, tungsten oxide, zinc oxide, as well as LiVO2, Li2VO4, Li4Ti5O 12 and composite oxides such as niobium titanium oxides. These negative electrode active materials may be used alone or in combination of two or more.
[0050] In the case of a sodium ion secondary battery, among the negative electrode active materials in the case of the lithium ion secondary battery described above, a negative electrode active material that does not contain lithium atoms and a negative electrode active material in which lithium atoms are replaced with sodium atoms may be used. Note that, when the negative electrode active material is lithium or a lithium alloy, or sodium or a sodium alloy, it may be used as an electrode without using a current collector.
[0051] When an electrode using an organic sulfur-based electrode active material as an electrode active material is used as a negative electrode and a counter electrode is a positive electrode, a known positive electrode active material to be used in the case of a lithium ion secondary battery is, for example, lithium Contains Examples of the lithium transition metal composite oxide include transition metal complex oxides, lithium-containing transition metal phosphate compounds, and lithium-containing silicate compounds. The transition metals of the lithium transition metal composite oxides are preferably vanadium, titanium, chromium, manganese, iron, cobalt, nickel, copper, and the like. Specific examples of the lithium transition metal composite oxide include lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, and Li2MnO3, and those in which a part of the transition metal atoms that are the main components of these lithium transition metal composite oxides is replaced with other metals such as aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, lithium, nickel, copper, zinc, magnesium, gallium, and zirconium. Specific examples of the replaced ones include Li 1.1 Mn 1.8 Mg 0.1 O4, Li 1.1 Mn 1.85 Al 0.05 O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.5 Mn 0.5 O2, LiNi 0.80 Co 0.17 Al 0.03 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O 2、 LiMn 1.8 Al 0.2 O4, LiMn 1.5 Ni 0.5Examples of the transition metal of the lithium-containing transition metal phosphate compound include vanadium, titanium, manganese, iron, cobalt, nickel, and the like. Specific examples include LiFePO4, LiMnO4, and Li2MnO3-LiMO2 (M=Co, Ni, Mn). X Fe 1-X Examples of the lithium-containing silicate compound include iron phosphate compounds such as PO4, cobalt phosphate compounds such as LiCoPO4, lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main component is replaced with other metals such as aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, lithium, nickel, copper, zinc, magnesium, gallium, zirconium, and niobium, and vanadium phosphate compounds such as Li3V2(PO4)3. Examples of the lithium-containing silicate compound include Li2FeSiO4. These compounds may be used alone or in combination of two or more.
[0052] In the case of a sodium ion secondary battery, a positive electrode active material in which the lithium atoms of the positive electrode active material in the above-mentioned lithium ion secondary battery are replaced with sodium atoms may be used.
[0053] The counter electrode can be manufactured by replacing the above-mentioned organic sulfur-based electrode active material with the above-mentioned known negative electrode active material or known positive electrode active material. In addition, when an electrode using an organic sulfur-based electrode active material as an electrode active material is used as a positive electrode, and the counter electrode is a negative electrode using a compound that does not contain lithium as a negative electrode active material, neither the positive electrode nor the negative electrode contains lithium. For this reason, a lithium pre-doping process is required to insert lithium into either or both of the negative electrode and the positive electrode in advance. The pre-doping method of lithium may be according to a known method. For example, when doping lithium into the negative electrode, a method of inserting lithium by an electrolytic doping method in which a half cell is assembled using metallic lithium as the counter electrode and lithium is electrochemically doped, or a method of inserting lithium by a pasting pre-doping method in which a metallic lithium foil is pasted on the electrode and then left in an electrolyte solution to dope the electrode by utilizing the diffusion of lithium into the electrode, can be mentioned. In addition, when pre-doping lithium into the positive electrode, the above-mentioned electrolytic doping method or pasting pre-doping method can be used.
[0054] Examples of the nonaqueous electrolyte of the nonaqueous electrolyte secondary battery of the present invention include a liquid electrolyte obtained by dissolving a supporting electrolyte in an organic solvent, a polymer gel electrolyte obtained by dissolving a supporting electrolyte in an organic solvent and gelling it with a polymer, a pure polymer electrolyte containing no organic solvent and in which a supporting electrolyte is dispersed in a polymer, a hydride-based solid electrolyte, and an inorganic solid electrolyte.
[0055] As supporting electrolytes used in liquid electrolytes and polymer gel electrolytes, in the case of lithium-ion secondary batteries, for example, conventionally known lithium salts are used, such as LiPF6, LiBF4, LiAsF6, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, LiB(C2O4)2, LiBF2(C2O4), LiSbF6, LiSiF5, LiSCN, LiClO4, LiCl, LiF, LiBr, LiI, LiAlF4, LiAlCl4, LiPO2F2, and derivatives thereof. Among these, it is preferable to use one or more selected from the group consisting of LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3 or its derivatives, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, and LiC(CF3SO2)3 or its derivatives. The content of the supporting electrolyte in the liquid electrolyte and the polymer gel electrolyte is preferably 0.5 mol / L to 7 mol / L, more preferably 0.8 mol / L to 1.8 mol / L.
[0056] As supporting electrolytes used in pure polymer electrolytes, in the case of lithium-ion secondary batteries, for example, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, LiB(C2O4)2 can be mentioned.
[0057] Examples of hydride-based solid electrolytes include LiBH4, LiBH4-LiI, LiBH4-P2S5, LiAlH4, Li3AlH6, etc.
[0058] As inorganic solid electrolytes, in the case of lithium-ion secondary batteries, Li 1+X A X B 2-x (PO4)3( A =Al, Ge, Sn, Hf, Zr, Sc, Y, B = Ti, Ge, Zn, 0 < x < 0.5), LiMPO4 (M = Mn, Fe, Co, Ni), lithium phosphate-based materials such as Li3PO4; Li3XO4 (X = As, V), Li 3+X AX B 1-X O4 (A = Si, Ge, Ti, B = P, As, V, 0 <x<0.6)、Li 4+X A X S 1-X O4 (A=B, Al, Ga, Cr, Fe, 0 <x<0.4)(A=Ni,Co、0<x<0.1)Li 4-3y Al y SiO4(0 <y<0.06)、Li 4-2y Zinc y GeO4(0 <y<0.25)、LiAlO2、Li2BO4、Li4XO4(X=Si,Ge,Ti)、リチウムチタネート(LiTiO2、LiTi2O4、Li4TiO4、Li2TiO3、Li2Ti3O7、Li4Ti5O 12 Lithium composite oxides such as LiBr, LiF, LiCl, LiPF6, LiBF4, and other compounds containing lithium and halogens; LiPON, LiN(SO2CF3)2, LiN(SO2C2F5)2, Li3N, LiN(SO2C3F7)2, and other compounds containing lithium and nitrogen; La 0.55 Li 0.35 Crystals with a perovskite structure that have lithium ion conductivity such as TiO3; Li7-La3Zr2O 13 Crystals with garnet structure such as 50Li4SiO4·50Li3BO 33 , 90Li3BO3·10Li2SO4, etc. glass; 70Li2S·30P2S5, 75Li2S·25P2S5, Li6PS5Cl, Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 , Li6PS5P 1.44 Cl3, Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 Lithium phosphorus sulfide crystals such as S4; 30Li2S 26B2S3 44LiI, 50Li2S 17P2S5 33LiBH, 50Li2S 50GeS2, 63Li2S 36SiS 2·Lithium phosphorus sulfide glasses such as 1Li3PO4, 57Li2S 38SiS2 5Li4SiO4, 70Li2S 50GeS2; Li7P3S 11 , Li 3.25 P 0.95 S4, Li 10 GeP2S 12 , Li 9.6 P3S 12 , Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3 Examples of the inorganic solid electrolyte include glass ceramics such as those mentioned above. The inorganic solid electrolyte may be coated with a polymer gel electrolyte. When an inorganic solid electrolyte is used, a layer of a polymer gel electrolyte may be provided between the inorganic solid electrolyte layer and the electrode.
[0059] In the case of a sodium ion secondary battery, a supporting electrolyte in which the lithium atoms in the above-mentioned lithium ion secondary battery are replaced with sodium atoms may be used.
[0060] The organic solvent used in the present invention for preparing the liquid non-aqueous electrolyte may be one that is generally used in liquid non-aqueous electrolytes, or may be a combination of two or more.Specific examples of the organic solvent include saturated cyclic carbonate compounds, saturated cyclic ester compounds, sulfoxide compounds, sulfone compounds, amide compounds, saturated chain carbonate compounds, chain ether compounds, cyclic ether compounds, and saturated chain ester compounds.
[0061] Among the organic solvents, saturated cyclic carbonate compounds, saturated cyclic ester compounds, sulfoxide compounds, sulfone compounds and amide compounds have high relative dielectric constants, and therefore play a role in increasing the dielectric constant of non-aqueous electrolytes, and saturated cyclic carbonate compounds are particularly preferred. Examples of such saturated cyclic carbonate compounds include ethylene carbonate, 1,2-propylene carbonate, 1,3-propylene carbonate, 1,2-butylene carbonate, 1,3-butylene carbonate, and 1,1-dimethylethylene carbonate. Examples of the saturated cyclic ester compounds include γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-hexanolactone, and δ-octanolactone. Examples of the sulfoxide compounds include dimethyl sulfoxide, diethyl sulfoxide, dipropyl sulfoxide, diphenyl sulfoxide, and thiophene. Examples of the sulfone compound include dimethyl sulfone, diethyl sulfone, dipropyl sulfone, diphenyl sulfone, sulfolane (also called tetramethylene sulfone), 3-methyl sulfolane, 3,4-dimethyl sulfolane, 3,4-diphenylmethyl sulfolane, sulfolene, 3-methyl sulfolene, 3-ethyl sulfolene, 3-bromomethyl sulfolene, etc., and sulfolane and tetramethyl sulfolane are preferred. Examples of the amide compound include N-methylpyrrolidone, dimethylformamide, dimethylacetamide, etc.
[0062] Among the organic solvents, saturated chain carbonate compounds, chain ether compounds, cyclic ether compounds, and saturated chain ester compounds can reduce the viscosity of the non-aqueous electrolyte, increase the mobility of electrolyte ions, and improve battery characteristics such as output density. In addition, saturated chain carbonate compounds are particularly preferred because they have low viscosity and can improve the performance of the non-aqueous electrolyte at low temperatures. Examples of saturated chain carbonate compounds include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl butyl carbonate, methyl-t-butyl carbonate, diisopropyl carbonate, and t-butyl propyl carbonate. Examples of the chain ether compound or cyclic ether compound include dimethoxyethane, ethoxymethoxyethane, diethoxyethane, tetrahydrofuran, dioxolane, dioxane, 1,2-bis(methoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)propane, ethylene glycol bis(trifluoroethyl)ether, propylene glycol bis(trifluoroethyl)ether, ethylene glycol bis(trifluoromethyl)ether, and diethylene glycol bis(trifluoroethyl)ether. Among these, dioxolane is preferred.
[0063] The saturated chain ester compound is preferably a monoester compound or a diester compound having a total carbon number in the molecule of 2 to 8. Specific examples of the compound include methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate, ethyl trimethylacetate, methyl malonate, ethyl malonate, methyl succinate, ethyl succinate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethylene glycol diacetyl, and propylene glycol diacetyl, and methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, and ethyl propionate are preferred.
[0064] Other examples of organic solvents that can be used in preparing the non-aqueous electrolyte include acetonitrile, propionitrile, nitromethane, and derivatives thereof, and various ionic liquids.
[0065] Examples of polymers used in polymer gel electrolytes include polyethylene oxide, polypropylene oxide, polyvinyl chloride, polyacrylonitrile, polymethyl methacrylate, polyethylene, polyvinylidene fluoride, polyhexafluoropropylene, etc. Examples of polymers used in pure polymer electrolytes include polyethylene oxide, polypropylene oxide, and polystyrene sulfonic acid. There are no particular limitations on the blending ratio in the gel electrolyte and the method of compounding, and it is sufficient to adopt a blending ratio and a method of compounding known in the art.
[0066] The non-aqueous electrolyte may further contain known additives such as an electrode film forming agent, an antioxidant, a flame retardant, an overcharge inhibitor, etc., in order to improve the battery life, safety, etc. When such additives are used, the amount thereof is usually 0.01 parts by mass to 10 parts by mass, and preferably 0.1 parts by mass to 5 parts by mass, based on the entire non-aqueous electrolyte.
[0067] The non-aqueous electrolyte secondary battery to which the present invention can be applied may have a separator between the positive electrode and the negative electrode. As the separator, a polymeric microporous film that is usually used in non-aqueous electrolyte secondary batteries can be used without any particular limitation. Examples of the film include films made of polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride, polyacrylonitrile, polyacrylamide, polytetrafluoroethylene, polysulfone, polyethersulfone, polycarbonate, polyamide, polyimide, polyethers such as polyethylene oxide and polypropylene oxide, various celluloses such as carboxymethyl cellulose and hydroxypropyl cellulose, polymer compounds mainly composed of poly(meth)acrylic acid and various esters thereof, derivatives thereof, copolymers or mixtures thereof, and the like. These films may be coated with ceramic materials such as alumina and silica, magnesium oxide, aramid resin, or polyvinylidene fluoride.
[0068] These films may be used alone or may be laminated to form a multi-layer film. Furthermore, various additives may be used in these films, and the type and content of the additives are not particularly limited. Among these films, in the method for producing a secondary battery, films made of polyethylene, polypropylene, polyvinylidene fluoride, polysulfone, or a mixture thereof are preferably used. In addition, when the non-aqueous electrolyte is a pure polymer electrolyte or an inorganic solid electrolyte, the separator may not be included.
[0069] The exterior member may be a laminate film or a metal container. The thickness of the exterior member is usually 0.5 mm or less, and preferably 0.3 mm or less. The shape of the exterior member may be flat (thin), rectangular, cylindrical, coin, button, or the like.
[0070] The laminate film may be a multi-layer film having a metal layer between resin films. The metal layer is preferably an aluminum foil or an aluminum alloy foil for weight reduction. The resin film may be made of a polymer material such as polypropylene, polyethylene, nylon, or polyethylene terephthalate. The laminate film may be sealed by heat fusion to form it into the shape of the exterior member.
[0071] The metal container can be made of, for example, stainless steel, aluminum, an aluminum alloy, etc. The aluminum alloy is preferably an alloy containing elements such as magnesium, zinc, silicon, etc. In the aluminum or aluminum alloy, by making the content of transition metals such as iron, copper, nickel, chromium, etc. 1% or less, it is possible to dramatically improve the long-term reliability and heat dissipation performance in a high-temperature environment. EXAMPLES
[0072] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited in any way by the following examples. In the examples, "parts" and "%" are by weight unless otherwise specified. In addition, the average particle size was measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model: LA-950V2) with water as the dispersion medium.
[0073] Raw material PAN mixture: 10 parts by mass of polyacrylonitrile powder (manufactured by Sigma-Aldrich, average particle diameter 200 μm, weight average molecular weight: approximately 150,000) and 30 parts by mass of sulfur powder (manufactured by Sigma-Aldrich, average particle diameter 200 μm) were mixed in a mortar to prepare the raw material for sulfur-modified polyacrylonitrile in Production Examples 1 to 3.
[0074] [Production Example 1] Sulfur-modified polyacrylonitrile was produced according to the method of the production example of JP 2013-054957 A. That is, 20 g of the raw material PAN mixture was placed in a bottomed cylindrical glass tube with an outer diameter of 45 mm and a length of 120 mm, and then a silicone plug having a gas inlet tube and a gas outlet tube was attached to the opening of the glass tube. After replacing the air inside the glass tube with nitrogen, the lower part of the glass tube was placed in a crucible-type electric furnace, and heated at 400 ° C. for 1 hour while introducing nitrogen from the gas inlet tube to remove the generated hydrogen sulfide. Note that the sulfur vapor condenses at the upper part or the lid of the glass tube and refluxes. After cooling, the product was placed in a glass tube oven and heated at 250 ° C. for 2 hours while vacuum suctioning to remove elemental sulfur. The obtained sulfur-modified product was pulverized using a ball mill, and then coarse particles were removed using a sieve with an opening of 40 μm to obtain sulfur-modified polyacrylonitrile SPAN1 with an average particle size of 10 μm.
[0075] [Production Example 2] Sulfur-modified polyacrylonitrile was produced by a method according to the example of JP 2014-022123 A. That is, a ribbon-type screw with an axis diameter of 5 mm, length of 600 mm, screw diameter of 42 mm, screw length of 450 mm, and screw pitch of 30 mm was inserted into a heat-resistant glass tube with an outer diameter of 50 mm, an inner diameter of 45 mm, and a length of 500 mm, and a silicone rubber stopper having a hole for the screw in the center and two holes for introducing or discharging gas at a position away from the center was attached to both ends of the glass tube, and a glass capillary made of heat-resistant glass with an outer diameter of 7 mm, an inner diameter of 5 mm, and a length of 100 mm was attached to the hole for introducing or discharging gas of the silicone rubber stopper to form a reactor. The reactor was attached to a tubular electric furnace with a heating portion of 300 mm, and the electric furnace was tilted so that the reactor was inclined at an angle of 5°. 30g of the raw PAN mixture was charged from the top of the inclined reactor, and the inside of the reactor was replaced with nitrogen gas. The temperature of the electric furnace was set to 420°C, and the reactor was heated at 0.5 revolutions per minute. During heating, nitrogen gas was fed from the glass capillary at the bottom of the reactor at a flow rate of 100ml / min, and the hydrogen sulfide gas produced was discharged from the glass capillary at the top. The sulfur that sublimed and adhered to the glass capillary at the top was appropriately heated to dissolve and reflux. The product that had passed through the heating portion of the reactor was cooled and then treated in the same manner as in Production Example 1 to obtain a sulfur-modified polyacrylonitrile powder SPAN2 having an average particle size of 10 μm.
[0076] [Production Example 3] The central part of a heat-resistant glass tube with an outer diameter of 10 mm and an inner diameter of 6 mm was expanded while being heated to produce a whole pipette-type glass core tube having an expanded part with an outer diameter of 30 mm and a length of 50 mm in the central part and capillaries with an outer diameter of 10 mm and a length of 150 mm at both ends. 5 g of the raw PAN mixture was placed in the expanded part of the furnace tube, the furnace tube was set so that it was inclined at 5°, the inside of the furnace tube was replaced with nitrogen gas, and then it was heated at 400°C for 1 hour while rotating at 1 revolution per minute. During heating, nitrogen gas was fed from the lower end of the furnace tube at a flow rate of 100 ml / min so that hydrogen sulfide gas generated from the upper end of the furnace tube could be discharged. The heating point of the furnace tube was the entire expanded part, but the sulfur that sublimated and adhered to the thin tube part was appropriately heated to dissolve and return to the expanded part. After cooling, the product was subjected to the same operation as in Production Example 1 to obtain a sulfur-modified polyacrylonitrile powder SPAN3 having an average particle size of 10 μm.
[0077] [Production Example 4] The same procedure as in Production Example 1 was repeated, except that 10 parts by mass of 27 μm to 32 μm polyethylene (manufactured by Corefront) and 30 parts by mass of sulfur powder (manufactured by Sigma-Aldrich, average particle size 200 μm) were mixed in a mortar instead of the raw PAN mixture, to obtain a polythienoacene compound powder SPE having an average particle size of 10 μm.
[0078] The sulfur content and specific surface area of SPAN1 to 3 and SPE are shown in Table 1. The sulfur content was calculated from the analysis results using a CHN analyzer (model: varioMICROcube, manufactured by Elementar Analysensysteme GmbH) capable of analyzing sulfur and oxygen. The specific surface area was measured in accordance with JIS Z8830 (method for measuring the specific surface area of powder (solid) by gas adsorption).
[0079] [Table 1]
[0080] [Preparation of negative electrode 1] A lithium metal having a thickness of 500 μm was cut to a predetermined size to prepare a disk-shaped negative electrode 1 .
[0081] [Preparation of Positive Electrode] The electrode active material, conductive additive, binder, and water as a solvent were mixed to obtain the composition shown in Table 2, and the slurry mixed using a rotation / revolution mixer was applied to a current collector by the doctor blade method and dried at 90°C for 3 hours. The electrode was then cut to a specified size and vacuum dried at 120°C for 2 hours to produce a disk-shaped electrode. Carbon-coated aluminum foil was used as the current collector for the organic sulfur-based electrode active material, and aluminum foil was used for the NCM.
[0082] Comparative electrode active material NCM:LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (manufactured by Nippon Chemical Industries) Conductive additive AB: Acetylene black (manufactured by Denka, product name: Denka Black Li-100) Binder ACB: Polyacrylic acid (polycarboxylic acid binder)
[0083] [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent consisting of 50 volume % ethylene carbonate and 50 volume % diethyl carbonate.
[0084] [Battery Assembly] The positive electrodes of Examples 1 to 9 and Comparative Examples 1 to 9, a disk-shaped negative electrode made of lithium metal with a thickness of 500 μm cut to a predetermined size, and a glass filter as a separator were sandwiched and held in a case. Then, the nonaqueous electrolyte prepared above was poured into the case, and the case was sealed to produce a nonaqueous electrolyte secondary battery (coin type with a diameter of 20 mm and a thickness of 3.2 mm). Note that the positive electrodes of Comparative Examples 8 to 9 had insufficient binding properties of the electrode active material mixture layer, and a battery could not be produced, so a charge / discharge test was not performed.
[0085] [Charge / Discharge Test Method] The nonaqueous electrolyte secondary battery was placed in a thermostatic chamber at 30° C., and five cycles of charge and discharge were performed at a charge rate of 0.1 C and a discharge rate of 0.1 C, with the charge cut-off voltage set to 3.0 V and the discharge cut-off voltage set to 1.0 V in Examples 1 to 9 and Comparative Examples 1 to 5 in which an organic sulfur-based electrode active material was used as the electrode active material, and the charge cut-off voltage set to 4.2 V and the discharge cut-off voltage set to 3.0 V in Comparative Examples 6 to 9 in which NCM was used as the electrode active material. Table 2 shows the discharge capacity A per mass of the electrode active material at the fifth cycle, and the discharge capacity B per mass of the electrode active material mixture layer.
[0086] [Table 2]
[0087] In the batteries of Examples 1 to 9 using an organic sulfur-based electrode active material, the discharge capacity B per mass of the electrode active material mixture layer is higher than that of the batteries of Comparative Examples 1 to 4, indicating that a good electrode active material mixture layer is formed even if the binder is reduced, and the charge / discharge capacity per unit mass of the electrode can be increased. Among the organic sulfur-based electrode active materials, the discharge capacity B is larger in sulfur-modified polyacrylonitrile than in polythienoacene compounds, and the discharge capacity B is particularly large in the case of sulfur-modified polyacrylonitrile (SPAN3) produced by heat-treating polyacrylonitrile and sulfur using a rotary heating vessel.
[0088] [Battery production] The positive electrodes of Examples 10, 11, and Comparative Examples 10 and 11, a disk-shaped negative electrode made of lithium metal with a thickness of 500 μm cut to a predetermined size, and a glass filter as a separator were sandwiched and held in a case. Thereafter, the nonaqueous electrolyte prepared above was poured into the case, and the case was hermetically sealed to prepare a nonaqueous electrolyte secondary battery (coin type with a diameter of 20 mm and a thickness of 3.2 mm).
[0089] [Charge / Discharge Test Method] The nonaqueous electrolyte secondary battery was placed in a thermostatic chamber at 0° C., and three cycles of charge and discharge were performed at a charge rate of 0.1 C and a discharge rate of 0.1 C with a charge cut-off voltage of 3.0 V and a discharge cut-off voltage of 1.0 V. Table 3 shows the discharge capacity C per mass of the electrode active material and the discharge capacity D per mass of the electrode active material mixture layer in the third cycle.
[0090] [Table 3]
[0091] In the batteries of Examples 10 and 11, the discharge capacity D, which is the discharge capacity per mass of the electrode active material mixture layer, is higher than that of the batteries of Comparative Examples 10 and 11, which indicates that a good electrode active material mixture layer is formed even when the binder is reduced, and that the charge / discharge capacity per unit mass of the electrode can be increased.
Claims
1. Current collector, and An electrode active material mixture layer containing an organic sulfur-based electrode active material, a conductive assistant, and a binder, the binder is contained in an amount of 0.01 mass % to 0.4 mass % relative to the total mass of the electrode active material mixture layer, and the electrode active material mixture layer is formed on the current collector.
2. The organic sulfur-based electrode active material has an average particle size of 0.1 μm to 50 μm and a specific surface area of 0.5 m2 measured by the BET method. 2 / g to 30m 2 2. The electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the molecular weight of the electrode is 1 / g.
3. An electrode for a non-aqueous electrolyte secondary battery as described in claim 1 or 2, wherein the organic sulfur-based electrode active material is selected from sulfur-modified polyacrylonitrile, sulfur-modified elastomer compound, sulfur-modified polynuclear aromatic ring compound, sulfur-modified pitch compound, polythienoacene compound, sulfur-modified polyether compound, sulfur-modified polyamide compound, sulfur-modified aliphatic hydrocarbon oxide or polycarbon sulfide.
4. The electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein the organic sulfur-based electrode active material is sulfur-modified polyacrylonitrile.
5. The electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein the binder is at least one selected from the group consisting of polyolefin-based binders, polydiene-based binders, polycarboxylic acid-based binders, polyether-based binders, polyvinyl alcohol-based binders, polyacrylonitrile-based binders, cellulose-based binders, polyester-based binders, and polyurethane-based binders.
6. A non-aqueous electrolyte secondary battery comprising the electrode for non-aqueous electrolyte secondary batteries according to any one of claims 1 to 5 as a positive electrode.
7. A non-aqueous electrolyte secondary battery, comprising the electrode for non-aqueous electrolyte secondary batteries according to any one of claims 1 to 5 as a negative electrode.
8. A step of adding an organic sulfur-based electrode active material, a conductive assistant, and a binder to a solvent to prepare a slurry; and A method for producing an electrode for a non-aqueous electrolyte secondary battery, comprising the step of applying the slurry to a current collector to form an electrode active material mixture layer, The binder is contained in an amount of 0.01% by mass to 0.4% by mass relative to the total mass of the electrode active material mixture layer.
9. The method for manufacturing an electrode for a non-aqueous electrolyte secondary battery described in claim 8, wherein the organic sulfur-based electrode active material is selected from sulfur-modified polyacrylonitrile, sulfur-modified elastomer compound, sulfur-modified polynuclear aromatic ring compound, sulfur-modified pitch compound, polythienoacene compound, sulfur-modified polyether compound, sulfur-modified polyamide compound, sulfur-modified aliphatic hydrocarbon oxide or polycarbon sulfide.
10. The method for producing an electrode for a non-aqueous electrolyte secondary battery according to claim 8 or 9, wherein the organic sulfur-based electrode active material is sulfur-modified polyacrylonitrile.
Citation Information
Patent Citations
Secondary battery using organic sulfur / metal charge-conducting material as the positive electrode
JP1998505705A
Nonaqueous secondary battery
JP2003151550A
Manufacturing method of electrode for chemical cell, and cell
JP2005310502A
Composite structure manufacturing method
JP2008184647A
Power storage device, and manufacturing method for electrode active material
JP2011028948A